Chemical speciation and combustion behavior of chromium (Cr) and vanadium (V) in coals. (15th November 2016) - Liu, Yuan; Liu, Guijian; Qi, Cuicui; Cheng, Siwei; Sun, Ruoyu
Highlights: Chemical forms and volatile behavior of Cr and V were studied in coals. Cr and V in studied coals are mainly associated with silicate matter. Volatilization ratios of Cr and V in coals decrease with the advance of coal rank. Abstract: Twenty-one coal samples of different coal ranks and one stone coal sample were collected from nine provinces in China, with an aim of studying the chemical speciation and combustion behavior of Cr and V in coals. The concentrations of Cr and V in studied coals range from 0.12 to 176 μg/g, and from 2.74 to 61.5 μg/g, respectively. Six operationally defined modes of occurrence of Cr and V are extracted from the coal using the sequential extraction procedure: water leachable, ion exchangeable, organic matter bound, carbonate bound, silicate bound and sulfide bound. Among these six modes, silicate bound Cr and V have the highest fractions. With the increase of coal rank, organic matter bound Cr and V show decline trends. We found that Cr and V are highly correlated in the coal samples, which may relate to their leading existence as silicate bound and organic bound forms. Both Cr and V exhibit medium to low volatility, due to their high association with silicate. The volatilization ratios of Cr and V in coals decrease with the advance of coal rank.